Formación de maestros(as) en América Latina: algunos problemas y perspectivas para este tiempo (2015)
This paper discusses the training of teachers, taking into consideration certain contemporary social features that determine both school and teaching positions in Latin America. In order to describe the contemporary challenges of teacher training, three problems are highlighted: the first one is related to the expansion of the right agenda (increased number of mandatory years of education, recognition of intercultural values, and focus on memory studies) and its effects on teacher training. The second problem analyzes public discourses that describe those students who plan to become teachers. The third problem focuses on a central theme in reviewing the current teacher training agenda, i.e. the relevance of both regional and local perspectives as a political and pedagogical problem. Thus, the three problems analyzed here help to identify new issues in the field of educational policy whileevidencing the importance of thinking about new pedagogies.